The Rhetorical Design of Isaiah 40-48/55 : Zion's Incomparable Saviour and His Servants - der, Lugt, P. van, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2022., 2022)
In this volume, Pieter van der Lugt offers a comprehensive analysis of the rhetorical structure of Isaiah. As in his previous studies on the Book of Job and the Psalter the author demonstrates that classical Hebrew poetry displays a well-defined structure consisting of balanced main parts (cantos) and subdivision into strophes. This rhetorical starting point is of crucial importance for the delimitation of the individual poems in Isaiah 40-48 and in many cases determines their interpretation. Subsequently, it is demonstrated that the successive compositions form well-defined and coherent cycles of poems.